2014
DOI: 10.1139/bcb-2013-0071
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-dependent transcriptional control in L6 rat myotubes is associated with modulation of histone acetylation and accumulation of the histone variant H2A.Z in the proximity of the transcriptional start site

Abstract: Besides its direct metabolic effects, insulin induces transcriptional alterations in its target tissues. However, whether such changes are accompanied by epigenetic changes on the chromatin template encompassing insulin responsive genes is unclear. Here, mRNA levels of insulin-responsive genes hexokinase 2 (Hk2), insulin receptor substrate (Irs2), and the PI3K subunit p85β (Pik3r2) were compared in control versus insulin-stimulated L6 myotubes. Chromatin immunoprecipitation (ChIP) was performed with antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…2D) indicated that ARP6/H2A.Z operates genetically downstream of HDA9. Furthermore, studies in rat (47) and yeast (48) demonstrated that histone acetylation levels positively correlate with H2A.Z occupancy. Taking this information into consideration, we hypothesized that HDA9-mediated H3K9K14 deacetylation at warm temperature conditions could modulate H2A.Z occupancy in Arabidopsis as well, allowing for PIF4 binding followed by thermal induction of YUC8 expression.…”
Section: Resultsmentioning
confidence: 99%
“…2D) indicated that ARP6/H2A.Z operates genetically downstream of HDA9. Furthermore, studies in rat (47) and yeast (48) demonstrated that histone acetylation levels positively correlate with H2A.Z occupancy. Taking this information into consideration, we hypothesized that HDA9-mediated H3K9K14 deacetylation at warm temperature conditions could modulate H2A.Z occupancy in Arabidopsis as well, allowing for PIF4 binding followed by thermal induction of YUC8 expression.…”
Section: Resultsmentioning
confidence: 99%
“…To amplify nuclear and mitochondrial genomic DNA, we used sonicated DNA prepared as previously described 15 . Briefly, cell culture medium was removed and cells were washed twice with ice-cold PBS before cross-linking for 10 minutes with 1% formaldehyde in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Acetylated H2A.Z and H3K9/14 acetylation at the promoter of hexokinase 2 ( HK2 ) increased its expression by twofolds in response to insulin. Similarly, treating rat L6 myotubes with insulin repressed IRS2 and PIK3R2 expression and treatment with trichostatin, a potent and reversible inhibitor of histone deacetylase, resulted in increased histone acetylation at the promoters of Irs2 and Pik3R2 and increased their expression 64 . HDAC6 impairs glucocorticoid‐induced hepatic glucose homeostasis by overexpressing Pepck, G6P and pyruvate carboxylase by changing H4K8 acetylation at the PEPCK gene promoter.…”
Section: Histone Modificationsmentioning
confidence: 99%